THE GOALS AND OBJECTIVES OF TEACHING ENGLISH LANGUAGE AT PRESCHOOL LEVEL - Nuraliyeva Ozoda (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract The teaching of any subject becomes much useful and more systematic only when the teacher is fully aware of the aims and values of instruction of that subject since the core principle of any teaching is “know what you do and only do what you know.” Hence it is essential to understand the aims and values of the teaching of English.